A Systematic Review of the Effectiveness of Environmental Awareness Interventions - Campbell, Monica (Can J Public Health, 2000)
Purpose: To evaluate and summarize evidence on the effectiveness of interventions available to public health staff regarding the protection of the public from environmental risks. Method: This systematic review involved a comprehensive literature search, screening for relevance, quality assessment of relevant studies, data extraction and synthesis. Results: Fourteen of 65 relevant studies were of ‘moderate’ or ‘strong’ quality. Intervention types in these 14 studies included: mass campaign, counselling, school curriculum, educational sessions, and distribution of printed materials. Short-term improvements in awareness or knowledge were observed in 13 of the 14 studies. Eight of 13 studies that examined behavioural outcomes observed short-term improvements in self-reported behavioural outcomes. Conclusions: Positive short-term changes in health-protective awareness, knowledge and selfreported behaviour appear to be associated with relatively intensive interventions that use multiple methods and settings, and/or are delivered over multiple sessions.